Synthesis and Properties of a Water-Soluble Ureide Derived from Gаlodif and Succinic Acid; Russian Journal of Organic Chemistry; Vol. 59, No. 9 - Kuksenok V. Yu. Vera Yurievna; Cui Yanwen; Shtrykova V. V. Viktoriya Viktorovna; Filimonov V. D. Viktor Dmitrievich; Shushpanova T. V. Tamara Vladimirovna (2023, 2023)
Title screen